2021
DOI: 10.11604/pamj.2021.39.284.30954
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of a urethral prolapse in a 6-year-old girl: a case report

Abstract: Urethral prolapse is a very rare disease, which is most often found in prepubescent girls. It occurs in about one over 5000 girls in the context of a chronic cough or any situation that increases abdominal pressure. It is often associated with diagnostic confusion, which delays management. We report the case of a 6-year-old child brought in urgently by her parents for a minimal genital hemorrhage and presence of a mass protruding from the vulva. In the hypothesis of a urethral prolapse, a medical treatment (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…Factors that increase the risk of UP include chronic constipation and coughing. These factors support the theory of increased intraabdominal pressure as a contributing mechanism [ 11 ]. Previous studies reported that the occurrence of UP increased with lower Body Mass Indexes in children [ 12 ].…”
Section: Clinical Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Factors that increase the risk of UP include chronic constipation and coughing. These factors support the theory of increased intraabdominal pressure as a contributing mechanism [ 11 ]. Previous studies reported that the occurrence of UP increased with lower Body Mass Indexes in children [ 12 ].…”
Section: Clinical Discussionsupporting
confidence: 83%
“…However, some patients do not experience any symptoms. Genital bleeding in prepubescent girls often triggers panic among parents and can lead to medicolegal and social concerns requiring the exclusion of sexual abuse [ 11 , 21 ]. The diagnosis of urethral prolapse relies on the physical examination and is made by identification of a soft circular mass of tissue surrounding the urethral meatus which is usually in the middle and separated from the vaginal opening [ 10 , 16 , 22 , 23 ].…”
Section: Clinical Discussionmentioning
confidence: 99%